Determinants of customers choices on online-enabled transportation services amidst the Covid-19 pandemic - Julianne D. Macababayao, April Rose L. Villanueva, Ma. Patricia V. Yanguas 4 0 16; 5
u
Research Paper: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2